Research on Curriculum Teaching Reform and Practice Based on OBE Concept - Taking the Course of "Urban Rail Transit Operation Organization" as an Example (Contemporary Education and Teaching Research, 2023)
In order to implement the implementation plan of China's higher vocational education reform and strengthen the skill cultivation of vocational students, this article adopts the teaching philosophy of "student-centered, output oriented, and continuous improvement" to reform and practice the curriculum organization, curriculum content, teaching methods, and curriculum evaluation. The teaching objectives support the specification of talent cultivation, the teaching content aligns with the job requirements of enterprise positions, the teaching methods reflect student-centered, the assessment and evaluation focus on the combination of process evaluation, professional literacy and ideological and political evaluation, and the achievement of course objectives. It not only focuses on students' understanding of theoretical knowledge, but also emphasizes the training of practical skills, and emphasizes the cultivation of students' quality. Practice has proven that this method effectively enhances students' awareness of autonomous learning and significantly improves teaching effectiveness.